Psychological distress, emotion regulation, neuroticism, and sexual relationship on patients with temporary ejaculation failure in vitro fertilization-embryo transfer treatment - Zhang, Xinting; Yang, Lexia; Wang, Wei; Yang, Lejin (Frontiers in Psychology, 2023)
Objective: Temporary ejaculation failure on the oocyte retrieval day might leading interruption of the oocyte retrieval procedure. The present study aims to understand the psychosocial factor that affects men with temporary ejaculation failure (TEF) in Vitro fertilization-embryo transfer (IVF-ET) patients, and thus provide new ideas for optimal clinical treatment. Study Design: In a prospective study, the male patients during IVF treatment in a reproductive centre of a tertiary hospital in Shandong were divided into two groups, 70 men with TEF and 79 normal controls. General population sociology and clinical disease were investigated, and the Kessler 10 scale, emotion regulation questionnaire, big five inventory questionnaire, and sex subscale of marriage quality were used to assess the psychological distress, emotion regulation, neuroticism and satisfaction with sexual life. Results: The scores of perceived distress and neuroticism of the TEF group were higher than the non-TEF group (p<0.001), and cognitive reappraisal and sexual relationship were significantly lower than those in the non-TEF group (p<0.001). Psychological distress (OR 1.130, p=0.031), and neuroticism (OR 1.096, p=0.050) as risk factors for TEF, while cognitive reappraisal (OR 0.883, p=0.004) and sexual relationship (OR 0.712, p<0.001) was protective factors. Conclusion: The present study demonstrates that psychosocial factors influence TEF in IVF patients, which provides the basis for the prevention of the occurrence of TEF in a male undergoing IVF-ET.